(untitled) (Journal of Economic Research & Business Administration, 2017)
Article is devoted to cost accounting problems on production and groups of costs. In article are considered in a survey type of classification of costs and group of costs in an interpretation of various authors. Aspects of concepts of the cost accounting and calculation of products constantly costs in the agenda of discussions of scientists and practicing. Moreover and in practice this problem is important, especially in the conditions of development of modern business. The necessity of classification of production costs is caused by cost management tasks in the companies with identification of objects, the existing cost groups and processes of their forming. Classification of costs shall answer the main task – to be based on the signs allowing to differentiate costs for management of them for the purpose of minimization of costs per unit of products.